Education for All: Gardner's Multiple Intelligences Theory - Emst-Slavit, Gisela (2001)
In the last years the Theory of the Multiple Intelligences developed by Howard Gardner has had a tremendous impact in elementary and secondary classrooms in the United States. Gardner(1983) defines intelligence as the ability to solve a problem or fashion a product that is valued in one or more cultural settings. His definition expands our understanding of "intelligence" beyond the familiar linguistic and Logical-mathematical intelligences, to include the spatial, musical,bodily-kinesthetic, naturalist. interpersonal, and intrapersonal intelligences. This new wayof conceptualizing human intelligence has profound implications for educators whose task needs to include the identification and nourishment of the different talents brought by al students.